(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify the epidemiological profile of people with neurotrophic ulcers resulting from leprosy, through a clinical study with a quantitative approach, characterized by the use of quantification in data collection and subsequent treatment by statistical techniques. It was carried out on the premises of the Centro Maria Imaculada, a reference center for leprosy in the municipality of Teresina, Northeast region of Brazil. The average age was 54.4 years, 70% of the participants were male, the majority, 60.0% had less than eight years of formal education, 60% of the income consisted of retirement and 50% received two salaries -minimum monthly, 50% of the race was mixed race and Piauí was the state of residence of all and 70.0% of the individuals had SAH as associated comorbidities. The average time of evolution of the neurotrophic ulcer, in months, was 101.8. 30.0% of the lesions were in the hallux. These findings reflect the profile of individuals with various limitations and unfavorable socioeconomic situations, which reinforce the association between poverty and leprosy, generating the need for continuous training of health professionals who provide care to patients with leprosy, at all levels of health care.